Vitamin D mediates the relationship between placental cathelicidin and group B streptococcus colonization during pregnancy. (June 2017) - Akoh, Christine C.; Pressman, Eva K.; Whisner, Corrie M.; Thomas, Carrie; Cao, Chang; Kent, Tera; Cooper, Elizabeth; O'Brien, Kimberly O.
Highlights: Recto-vaginal GBS colonization is associated with lower placental CAMP mRNA. Placental CAMP mRNA is positively correlated with CYP27B1 mRNA. Placental CYP27B1 mRNA and cubilin mRNA are lower in those with GBS. Vitamin D status may increase susceptibility to maternal-fetal infections. Abstract: Vitamin D is thought to modulate innate immune responses, and recent studies have highlighted the autocrine and paracrine functions of vitamin D in the placenta. Our objective was to determine the relationship between maternal vitamin D status and placental antimicrobial peptide (AMP) expression in a group of racially and ethnically diverse pregnant adolescents. In this study, 158 pregnant adolescents were recruited from the Rochester Adolescent Maternity Program (RAMP) in Rochester, NY. Maternal serum concentrations of the vitamin D biomarkers, 25-hydroxyvitamin D (25(OH)D) and 1, 25-dihydroxyvitamin D (1, 25(OH)2 D), were measured at mid-gestation (∼26 weeks) and at delivery. At the placental level, vitamin D regulatory proteins (cubilin, megalin, 1α-hydroxylase (CYP27B1), 24-hydroxylase (CYP24A1), vitamin D receptor (VDR)) and AMPs (cathelicidin and hepcidin) were analyzed using quantitative PCR and western blot techniques. Placental CYP27B1 mRNA expression was significantly positively associated with both placental cathelicidin mRNA expression (P < 0.0001) and placental hepcidin mRNA expression (P = 0.002). In teens with positive recto-vaginal group B streptococcus (GBS) colonization, placental mRNA expression of cathelicidin (P = 0.007), cubilin (P = 0.03), and CYP27B1 (P = 0.04) were significantly lower compared to those who tested negative for this infection. A mediation analysis showed that the indirect relationship between GBS colonization and placental cathelicidin mRNA expression was mediated by the placental mRNA expression of the vitamin D proteins cubilin and CYP27B1 (P = 0.02). Additional research is needed to identify the role and relative contributions of placental and systemic vitamin D metabolites in relation to potentially pathogenic microorganisms which may be present during pregnancy.